A synergistic biorefinery based on catalytic conversion of lignin prior to cellulose starting from lignocellulosic biomass. Issue 3 (10th December 2014) - Parsell, Trenton; Yohe, Sara; Degenstein, John; Jarrell, Tiffany; Klein, Ian; Gencer, Emre; Hewetson, Barron; Hurt, Matt; Kim, Jeong Im; Choudhari, Harshavardhan; Saha, Basudeb; Meilan, Richard; et al.
Abstract : One step conversion of lignin from intact biomass to two phenol products, improving access to aromatics and fuels. Abstract : Current biomass utilization processes do not make use of lignin beyond its heat value. Here we report on a bimetallic Zn/Pd/C catalyst that converts lignin in intact lignocellulosic biomass directly into two methoxyphenol products, leaving behind the carbohydrates as a solid residue. Genetically modified poplar enhanced in syringyl (S) monomer content yields only a single product, dihydroeugenol. Lignin-derived methoxyphenols can be deoxygenated further to propylcyclohexane. The leftover carbohydrate residue is hydrolyzed by cellulases to give glucose in 95% yield, which is comparable to lignin-free cellulose (solka floc). New conversion pathways to useful fuels and chemicals are proposed based on the efficient conversion of lignin into intact hydrocarbons.